Peran Supervisi Akademik Kepala Madrasah dalam Meningkatkan Kinerja Guru A Literature Review - Hasan, Aiza Nirmala; Hariri, Hasan (Program Studi Magister Manajemen Pendidikan, 2023)
Abstract: The Role of Academic Supervision of the Head of Madrasah in Improving Teacher Performance. In the current era of globalization, this study seeks to investigate how the role of supervision can improve the performance of madrasah teachers. According to the study's findings, the leadership of the head supervisor of madrasah heads is essential for student character development and improving teacher performance, encouraging reforms to improve education standards, and improving learning effectiveness. The need to build supervisory leadership in madrasah can be determined using a scale that has been created by several studies to assess the leadership skills of the supervisory role of madrasah administrators. It is recommended that madrasah managers pay attention to the leadership role of supervisors in fostering student character development, fostering change, and improving teacher performance in order to improve the level of education and success of madrasah.Keywords: Academic, Head of Madrasah, Leadership Supervision role.DOI: 10.23960/jmmp .v11.i1.2023.03